Rare case reports of ruptured ectopic pregnancy - Paul, Dhrubal Prasad; Debbarma, Dibakar; Rakshit, Ashis Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Two patients of 30-35 years of age presented in Gynecological emergency of Agartala Government Medical College at unstable condition with the diagnosis of ruptured ectopic pregnancy. Both the cases were taken for emergency laparotomy after initial resuscitation, investigations & arrangement of blood products. In both the cases rupture were found in right side and hence right sided salpingectomy done in both the cases. Both the tubes (affected) after laparotomy were sent for histopathological examination where both the reports came to be partial mole. Ectopic hydatiform mole (either complete or partial) are rare events, among these Ectopic partial moles are rarer. Both the cases were in regular follow up & ß-HCG levels came to the base level within 6-7 wks. The 1st case became pregnant after 9 months of laparotomy.